2018
DOI: 10.3386/w24770
|View full text |Cite
|
Sign up to set email alerts
|

Family Income and the Intergenerational Transmission of Voting Behavior: Evidence from an Income Intervention

Abstract: Despite clear evidence of an income gradient in political participation, research has not been able to isolate the effects of income on voting from other household characteristics. We investigate how exogenous unconditional cash transfers affected voting in US elections across two generations from the same household. The results confirm that there is strong inter-generational correlation in voting across parents and their children. We also show-consistent with theorythat household receipt of unconditional cash… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 40 publications
6
36
0
Order By: Relevance
“…This would be consistent with the early argument within this largely theoretical literature that, "the more important a political orientation is in the behavior of adults, the earlier it will be found in the learning of the child" (Greenstein, 1965;Akee et al, 2018). While it's likely that the economic channels have similarly more pronounced effects when received earlier, in line with Chetty et al (2016) and Chetty and Hendren (2018a), it's also plausible that these could be operating indirectly through the psychological channels (e.g., a common set of norms and values, instilled earlier in childhood, leading to improved graduation and political participation).…”
Section: Psychological Channelssupporting
confidence: 85%
See 1 more Smart Citation
“…This would be consistent with the early argument within this largely theoretical literature that, "the more important a political orientation is in the behavior of adults, the earlier it will be found in the learning of the child" (Greenstein, 1965;Akee et al, 2018). While it's likely that the economic channels have similarly more pronounced effects when received earlier, in line with Chetty et al (2016) and Chetty and Hendren (2018a), it's also plausible that these could be operating indirectly through the psychological channels (e.g., a common set of norms and values, instilled earlier in childhood, leading to improved graduation and political participation).…”
Section: Psychological Channelssupporting
confidence: 85%
“…Second, we examine changes in parents' outcomes and find these are unlikely to drive the voting results, as the intervention had no significant impact on their voting behavior. Third, we argue that improvements in high school graduation and labor market outcomes (earnings and employment) in adulthood are plausible mechanisms, as Chyn (2018) shows that the effects of demolition on these outcomes are large and prior studies show that these outcomes affect voting (Sondheimer and Green, 2010;Akee et al, 2018). Finally, we discuss more psychological channels, such as potential changes in beliefs and norms that come with moving to a new neighborhood, though we are limited in the data that can shed light on these mechanisms.…”
Section: Introductionmentioning
confidence: 87%
“…Many of our examples come from access to welfare and health benefits, but these are not the only venues in which poor, sick, and old citizens are challenged in their interactions with the state. For instance, people are less likely to vote if they have fewer financial resources (Akee et al ), mental and physical health problems (Burden et al ), and age‐related cognitive decline (Burden et al ), which may be partly explained by reduced executive functioning.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has innovated by placing greater emphasis on identification of causal impacts. For example, studies have found that changes in family income (Akee et al 2018), education-related interventions (Sondheimer, Milstein, and Green 2010;Holbein 2017), and neighborhood relocation (Chyn and Haggag 2019) have important impacts on later-life voter participation. Fewer studies have produced credible estimates of causal impacts of early-life conditions on partisanship.…”
mentioning
confidence: 99%